Evaluating signs in a public library (National Library of Singapore at Stamford Road) - Neo, Tiong Seng. (2011)
This paper is about the evaluation of signs in a public library to determine the impact they have on users' search behaviour, if any, and to recommend a set of guidelines for implementing signage at the National Library. A qualitative approach was used to gather data through interviews conducted with a sample of fifty users of the library. Interview results showed that most users were satisfied with the existing signage but improvements could be made in some areas. Some users wished to see a more professional image portrayed by the library, through the installation of professionally produced signs, rather than the present mix of professionally made signs with signs made in-house by staff. This tied in with the wish of some users to see more coordination and uniformity of signs in terms of colour, size and style. In addition to the interviews, the literature review highlighted some of the practices of other institutions and libraries, which the National Library could adapt and implement. Recommendations in this paper include careful planning of signage projects, hiring a professional design consultant (if funds are available), and suggestions regarding the placement, size, colour, text, graphical information, installation, materials and techniques, and the evaluation and maintenance of signs and the use of a manual of signs.